PENGARUH MEDIA PEMBELAJARAN SPARKOL VIDEOSCRIBE DALAM MENINGKATKAN HASIL PADA MATA PELAJARAN SISTEM KOMPUTER - indri Rahma Dewi Safitri (Institut Pendidikan dan Bahasa Invada, 2022)
The purpose of this study was to determine the effect of mediaSparkol VideoScribe learning in improving Student Learning Outcomes in Computer Systems subjects with number system material. The research method used is the survey method. The population used in this study were students of class X Multimedia 1 SMK Manba'ul 'Ulum Cirebon with a sample of 40 students. The sampling technique used in this study is purposive sampling, in which a sampling technique takes into account thecertain. The data collection techniques used by the researcher are research (survey and observation), literature/documentation studies, questionnaires/questionnaires, and interviews. The results of the study show: 1) The application of sparkol videoscribe learning media in teaching and learning activities in the classroom, students who are assisted with learning media have a much more significant increase compared to conventional methods. That way, with the sparkol videoscribe media, the material presented will be much more concrete and interesting which will produce output, one of which is increased learning outcomes; 2) Sparkol VideoScribe learning media has an effect on improving student learning outcomes. With that, there is a positive and significant relationship between the sparkol videoscribe learning media and student learning outcomes, where the value of R = 0.356 and R Square is 0.287 (0.536 x 0.536 = 0.287) which means that the contribution of Sparkol VideoScribe (X) on Student Learning Outcomes (Y) is 28.8%.